2013
DOI: 10.1186/1479-5868-10-102
|View full text |Cite
|
Sign up to set email alerts
|

Screen time use in children under 3 years old: a systematic review of correlates

Abstract: BackgroundA large percentage (68%) of children under age 3 use screen media, such as television, DVDs and video games, on a daily basis. Research suggests that increased screen time in young children is linked to negative health outcomes, including increased BMI, decreased cognitive and language development and reduced academic success. Reviews on correlates of screen time for young children have included preschool age children and children up to age 7; however, none have focused specifically on correlates amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

41
281
6
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(347 citation statements)
references
References 52 publications
(325 reference statements)
41
281
6
19
Order By: Relevance
“…A 2013 review by Duch et al reported that 5 of the 12 included studies (58 %) of children <3 years old found television viewing time to be lower in high SEP households [132]. The other seven studies found no association.…”
Section: Television Viewing (Including Video and Computer Games)mentioning
confidence: 98%
“…A 2013 review by Duch et al reported that 5 of the 12 included studies (58 %) of children <3 years old found television viewing time to be lower in high SEP households [132]. The other seven studies found no association.…”
Section: Television Viewing (Including Video and Computer Games)mentioning
confidence: 98%
“…A systematic review showed that children's growth was also related to a longer time spent in front of the television 49 , and this exposure was associated with an excessive consumption of foods with a high energy density and low nutrient content 49,50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…A child's biological and demographic factors include sex, age, ethnicity, and firstborn status; while the family's biological or demographic factors include parental education, income, and age. 3 The AAP recommends that children watch TV only after the age of 2 years, and not exceeding 2 hours per day. 1 We found that 79 of 84 subjects started watching TV before 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Their developers persuade parents to provide them as educational tools for children. Duch et al 3 reported that 82% of children aged one year watched TV everyday; some children aged 2 years watched TV longer than two hours per day. They also found that as children grew older they tended to watch more TV.…”
mentioning
confidence: 99%
See 1 more Smart Citation